Financial literacy, financial behavior, and financial decision: The mediating role of investment intention among SMEs in Indonesia - Amin, Moh; Wardoyo, Cipto; Handayati, Puji; Winarno, Agung (The Economics and Finance Letters, 2026)
Financial literacy and financial behavior are two primary determinants of financial decision-making among small and medium enterprises (SMEs), and empirical research holds significant promise for entrepreneurship. Therefore, this study investigates these linkages and analyzes the mediating role of investment intention in promoting investment decisions among SMEs in Malang Raya, East Java, Indonesia. The research employed a quantitative methodology using partial least squares structural equation modeling (PLS-SEM) and was grounded in the Theory of Planned Behavior (TPB). A total of 310 halal-certified SME owners in Malang Raya participated in this study. The results reveal that financial literacy can influence investment; however, it does not necessarily promote investment decisions. Additionally, financial behavior showed a negative direct effect on investment decisions, but it contributes positively when mediated by intention. This finding confirms that investment intention can be a strong predictor of decision-making. The contributions of this study are twofold. First, it adds to the existing literature on the role of financial literacy and its components in supporting investment decisions, particularly within the context of entrepreneurship and SMEs. Second, it highlights the limited role of intention alone, suggesting that individual or organizational knowledge can directly influence behavior, and that intention is an integral part of behavior.